Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1097/ccm.0000000000004401
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal Membrane Oxygenation for Poisonings Reported to U.S. Poison Centers from 2000 to 2018: An Analysis of the National Poison Data System*

Abstract: Objectives: To assess trends in the use of extracorporeal membrane oxygenation for poisoning in the United States. Design: Retrospective cohort study. Setting: The National Poison Data System, the databased owned and managed by the American Association of Poison Control Centers, the organization that supports and accredits all 55 U.S. Poison Centers, 2000–2018. Patients: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
25
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 27 publications
5
25
1
Order By: Relevance
“…According to data published in 2018 by the Association of Poison Control Centers' National Poison Data System (NPDS), antidepressant exposures over the past 10 years have increased rapidly with the most frequently reported poisonings being bupropion and citalopram, with 14,824 and 8,169 cases respectively [3]. In another review, looking at ECMO cases reported to the NPDS, bupropion was the most common antidepressant in single-ingestion cases, further illustrating the seriousness of bupropion overdoses [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to data published in 2018 by the Association of Poison Control Centers' National Poison Data System (NPDS), antidepressant exposures over the past 10 years have increased rapidly with the most frequently reported poisonings being bupropion and citalopram, with 14,824 and 8,169 cases respectively [3]. In another review, looking at ECMO cases reported to the NPDS, bupropion was the most common antidepressant in single-ingestion cases, further illustrating the seriousness of bupropion overdoses [1].…”
Section: Discussionmentioning
confidence: 99%
“…Management of bupropion and citalopram poisonings remain largely supportive, though more invasive treatments have begun to emerge, such as ECMO [1]. Once conventional therapies with vasopressors and lipid emulsion (Intralipid ®, Baxter Healthcare Corp., Deerfield IL) failed to mitigate worsening multifaceted shock, our patient was given hydroxocobalamin, to temporarily alleviate vasoplegia, and placed on VA ECMO.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that ECMO has attracted more attention in severe poisoning, such as through irritant gases, PQ, and aluminum phosphide. [6][7][8] E CMO can preserve tissue perfusion by augmenting oxygenated venous blood via V-V ECMO, enhancing perfusion to critical organs, and improving oxygenation via V-A ECMO. L ung transplantation may be the most effective end-stage therapy, owing to irreversible pulmonary fi brosis induced by PQ, in which ECMO can be the transitional supportive therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, more invasive treatments, such as extracorporeal membrane oxygenation (ECMO) should be considered if profound shock or cardiac arrest develops (particularly if sufficient antibody doses are not immediately available), as ECMO has been successfully used to treat digoxin poisoning. 5 Again, we thank O'Brien and colleagues for highlighting their important case, and encourage other clinicians who encounter patients purporting to have taken candlenuts with cardiac symptoms to consider yellow oleander poisoning in their differential diagnosis.…”
Section: To the Editormentioning
confidence: 94%